Evaluation of two modalities of management of the pseudostem after the harvest on the growth, production and health of banana plants (Musa AAA) - Vargas, Alfonso (2010)
In order to evaluate 2 modalities of common use in the management of the pseudostem after the harvest of the mother plant, 2 experiments were performed during the year 2006 in commercial banana (Musa AAA, cv. Grande Naine) plantations in the Caribbean region of Costa Rica. The treatments in both experiments were: 1-periodic elimination and 2 total retention, until collapse, of the deteriorated tissue of the pseudostem after harvest. Growth, yield, diseases and insect-pest variables were measured. Except for the length of the second hand in experiment 1 (p = 0.0309), and of the sixth hand in experiment 2 (p = 0.0455), there were no differences between treatments in the remainder growth (p > 0.1480) and produc-tion (p > 0.0652) variables. Presence of Erwinia spp., soft rot was not observed. In both experiments, damage by larvae of Cosmopolites sordidus was observed, which nevertheless was of little magnitude and only differed between treatments (p = 0.0227) in experiment 2. Corm rotting associate of with black weevil was only observed in experiment 1, at a low value, and with no differences between treatments (p > 0.7574). The presence of Pseudococcus elisae and Periplaneta spp.was determined only in experiment 1; with both insects, the greater values (p < 0.0412) were observed in treatment 2 (total retention). The presence of scales and aphids was not observed in either experiment. Since there were not differences in growth and production between treatments, the selection of one of them would be given by risk factors associated with inse pest and/or common diseases to the banana crop.